Increased Sperm DNA Damage in Experimental Rat Varicocele Model and The Beneficial Effect of Varicocelectomy - Metin İshak Öztürk; Orhan Koca; Muzaffer Oğuz Keleş; Seda Yılmaz; Muhammet Ihsan Karaman (International Journal of Fertility and Sterility, 2012)
Background Varicocele, the abnormal dilatation of the veins in the pampiniform plexus is commonly seen in infertile patients. In this study, we aim to examine sperm DNA damage after the creation of experimental varicocele in rats and to observe the change of this damage after a varicocelectomy. Materials and Methods In this experimental study, a total of 30 adult male Wistar albino rats were divided into three groups. The 10 rats in group 1 underwent a sham operation, an experimental varicocele was created in both the10 rats in group 2 and the 10 rats in group 3 (a total of 20 rats). While the rats of group 2 were sacrificed after four weeks, the rats in group 3 underwent a varicocelectomy after four weeks and were sacrificed four weeks after the varicocelectomy to observe its effects. Sperm DNA fragmentation was assessed with a Halomax® kit. The DNA Fragmentation Index (DFI) was calculated and the groups were compared according to their DFI. Statistical analysis was performed using the Mann-Whitney U test. Results Median sperm DFI was 17.6 (range: 7.6) in the right testicle and 18.3 (range: 6.8) in the left testicle in the control group; 30.7 (range: 8.8) in the right testicle and 31.8 (range: 9.6) in the left testicle in the varicocele group; 27.1 (range: 8.1) in the right testicle and 28.6 (range: 8.9) in the left testicle in the varicocelectomy group. DNA damage in both right and left testicles was statistically significant between the three groups (p < 0.05). Conclusion The results of this study show that varicocele leads to increased sperm DNA damage and this damage is decreased by varicocelectomy.